The Effect of the Big Book Media Usage to Simple Sentences’ Reading Ability for Third Grader with Intellectual Disability on Elementary School for Special Needs - Putri Karlis Ramadhani; Usep Kustiawan (Department of Special Education, 2017)
Child with mild intellectual disability has a resistance of 50-80 IQ intelligence below normal IQ. The purpose of this study is to analyze the effect of the big book media usage towards reading ability of simple sentences for students with mild intellectual disability. The study used the pre-experimental method with one group pretest–posttest design. The data analysis was tested by wilcoxon signed ranks test with significant level 0.05 and 5 students as sample. The results found that there was the effect of the big book media usage towards reading ability of simple sentence for students with mild intellectual disability. Suggestions for the teachers to apply the big book media as complement in learning process for the students with mild intellectual disability.